Collaborative planning of subcontractors using the Last Planner System: a case study on a gas subcontractor in repetitive housing projects - Xavier Brioso; Karla Delgado-Martínez; Luis Bravo-Salomón (Anales de Edificación)
The efficient management of subcontractors turns into a challenge in contracts with fixed prices and short terms. Non-conformances due to poor deliverables are common, generating delays and cost overruns for all parties involved, especially for the main contractor. In addition, in recent years some collaborative systems have appeared, such as the Last Planner System (LPS), which has proven to be very efficient in the generation of value and the optimization of resources. However, there is still little information about successful results in the management of subcontractors. The main objective of this study is to propose a method that adapts the LPS for the management of the subcontract of natural gas facilities in highly repetitive housing projects, as well as to apply it successfully. The methodology was applied to a massive multi-family low-cost housing project in the city of Lima, Peru, which was modeled by using BIM technology. The most frequent root causes of non-conformances were determined for the first buildings, and this information was used for the collaborative planning of the following buildings. This allowed to determine the optimal sectioning, Takt Time Planning, subcontractor restrictions, weekly and daily planning, and finally, the lessons learned from the implementation of the LPS for future projects, which can be adapted to other types of subcontracts